A Novel Approach for Security Using RSA Parallelization Process - Kalburgi, Ayisha M; Jalapur, Shruti (2018 3rd IEEE International Conference on Recent Trends in Electronics, Information & Communication Technology (RTEICT), 2018)
Key exchange for cryptographic system is always a challenge. A private key algorithm is used to encipher and decipher the message, but after the symmetric key encrypts the message the digital envelope concept is used where the public key method or symmetric key algorithms are used to send the private key to the other party. A significant amount of research has focused on methods to improve the efficiency of cryptographic algorithms. Public key based cryptographic algorithms are usually considered as slower than their corresponding symmetric key based algorithms due to their root in modular arithmetic. So for encrypting the large message, symmetric key algorithms are used whereas for the relatively smaller key, asymmetric key algorithm is used. Here we are implementing this digital envelope system using asymmetric key algorithm. The goal is to improve the system by implementing the algorithm with parallelization using OpenMP on the GCC infrastructure.